Cobalt Single‐Atom Catalysts with High Stability for Selective Dehydrogenation of Formic Acid. Issue 37 (29th June 2020) - Li, Xiang; Surkus, Annette‐Enrica; Rabeah, Jabor; Anwar, Muhammad; Dastigir, Sarim; Junge, Henrik; Brückner, Angelika; Beller, Matthias
Abstract: Metal–organic framework (MOF)‐derived Co‐N‐C catalysts with isolated single cobalt atoms have been synthesized and compared with cobalt nanoparticles for formic acid dehydrogenation. The atomically dispersed Co‐N‐C catalyst achieves superior activity, better acid resistance, and improved long‐term stability compared with nanoparticles synthesized by a similar route. High‐angle annular dark‐field–scanning transmission electron microscopy, X‐ray photoelectron spectroscopy, electron paramagnetic resonance, and X‐ray absorption fine structure characterizations reveal the formation of Co II Nx centers as active sites. The optimal low‐cost catalyst is a promising candidate for liquid H2 generation. Abstract : The small print : Co‐N‐C single‐atom catalysts were derived from metal– organic frameworks and compared with related nanoparticles in the selective dehydrogenation of formic acid. The highly dispersed single Co II N x sites demonstrated improved reactivity and resistance to acid, constituting the current state‐of‐the‐art in low‐cost earth‐abundant catalysts for this transformation.